Tax Digitalization and Justice with Taxpayer Compliance and the Mediating Role of Tax Awareness - Supriyati, Supriyati; Oktarina, Dian; Rokhmania, Nur'aini; Prananjaya, Kadek Pranetha (Pandawan, 2025)
This study investigates the impact of tax information digitalization and tax fairness on taxpayer compliance, with tax awareness as a mediating variable. Taxpayer compliance is critical for government financial performance, yet tax revenues in Indonesia remain below target. Despite government efforts to improve tax compliance through reforms, internal and external taxpayer factors still significantly influence compliance behavior. The study focuses on the need for policy improvements to address these issues. While prior studies have analyzed tax compliance, few have examined the interplay between tax digitalization, fairness, and awareness in Indonesia. This research makes a unique contribution by investigating these variables in Surabaya, an industrial hub, offering a localized yet impactful perspective on tax compliance in a dynamic economic region. Using a survey of 200 taxpayers in Surabaya and discussions through a Focus Group Discussion with 15 participants, this research aims to provide insights into the effectiveness of government tax reform policies. The results indicate that digitalization of tax information, fairness, and awareness positively impact taxpayer compliance. Tax awareness strengthens the relationship between digitalization and compliance, but it does not mediate the effect of tax fairness on compliance. The findings suggest that continued efforts to enhance tax information systems and address fairness perceptions are essential for improving compliance.